REVIEW JURNAL : STUDI ETNOFARMASI TERHADAP PEMANFAATAN BAWANG PUTIH (Allium sativum) SEBAGAI TERAPI HERBAL HIPERTENSI - Nisful Lailatun Nadiroh; Dwi Roisiyah; Nailah Mutiara Wahid; Nungki Hatit Isafani; Jesika Diah Pitaloka; Iftitah Nakhlah Sani; Wishnu Eka Adiwinata; Muhammad Rizky Imami; Farrel Darian Hafiz Fathan; Ivan Charles S.Klau (Universitas Pendidikan Muhammadiyah Sorong, 2025)
Hypertension, or high blood pressure, is a chronic medical condition characterized by an increase in systolic blood pressure ≥140 mmHg and/or diastolic ≥90 mmHg based on two measurements at rest. In the treatment of hypertension, in addition to pharmacological treatment, complementary therapy approaches based on medicinal plants are starting to gain attention because they are considered safer. Garlic is one of the most widely studied because of its bioactive compound content which has pharmacological activity, including in lowering blood pressure and as a natural antioxidant. The review was conducted using the method of collecting several national research journals and previously published literature. The sources used in this journal review are several journals that have been accredited by SINTA and also literature from the last 5 years. The search for articles and research journals was carried out using article search engines such as PubMed, ResearchGate, Google, and Google Scholar. The journal review conducted this time aims to see and find out how much potential the garlic plant has to act as an antihypertensive. The sources used in this review are journals that have been accredited. The results of several literature studies found that there was an effect of giving garlic herbal medicine to hypertension sufferers. The conclusion is that giving garlic infusion can lower blood pressure in hypertension patients.